Comparison some of methods wavelet estimation for non parametric regression function with missing response variable at random - رشيد ظافر حسين; حمزة سعد كاظم (Journal of Economics and Administrative Sciences, 2016)
Abstract The problem of missing data represents a major obstacle before researchers in the process of data analysis in different fields since , this problem is a recurrent one in all fields of study including social , medical , astronomical and clinical experiments . The presence of such a problem within the data to be studied may influence negatively on the analysis and it may lead to misleading conclusions , together with the fact that these conclusions that result from a great bias caused by that problem in spite of the efficiency of wavelet methods but they are also affected by the missing of data , in addition to the impact of the problem of miss of accuracy estimation it is not possible to apply these methods because of the miss of one of its conditions which is dyadic sample size . According to the great impact resulted from the problem , many researchers who devoted their studies to process this problem , by using traditional methods in processing missing data , whereas the current research used imputation methods more efficient and effective to process missing data as a primary stage so that these data will be ready and available to wavelet application , as a result simulation experiment proved that the suggested methods (Nearset Nighbor Polynomial Wavelet) are more efficient and superior to other methods , this paper also includes the auto correction of boundaries problem by using local polynomial models , and using different threshold values in wavelet estimations